Post a New Question

Algebra 2

posted by on .

solve log2(3x-1)-log2(x-1)=log2(x+1)
i have absolutely no idea how to solve this. can anyone help me, please?

  • Algebra 2 - ,

    Start by grouping all the log terms together.

    log2(3x-1)-log2(x-1)-log2(x+1)=0

    log2[(3x-1)/(x-1)(x+1)]=0

    remove the log2

    [(3x-1)/(x-1)(x+1)]= 2^0 = 1

    solve for x

    I got x=3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question